2019
DOI: 10.1017/s1463423619000835
|View full text |Cite
|
Sign up to set email alerts
|

Preventing unintentional home injuries among children: exploring the perceptions of Iranian health professionals

Abstract: Background:Health professionals are key stakeholders who potentially have important roles in preventing unintentional child home injuries. This study aimed to identify facilitators and barriers to the prevention of unintentional child home injuries perceived by health professionals.Design:A generic qualitative study involving semi-structured interviews.Setting:The capital city of Iran.Method:Data for this study were collected through 28 in-depth interviews with health professionals. Purposive sampling was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Similar results were given in Germany by Foetinger et al [49]. In a large number of studies, the mother's employment was marked as a risk factor which increased the chances of children's accidental injuries [9,23,27,50]. This was explained by the unemployed mother's greater care for her children due to more free time.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar results were given in Germany by Foetinger et al [49]. In a large number of studies, the mother's employment was marked as a risk factor which increased the chances of children's accidental injuries [9,23,27,50]. This was explained by the unemployed mother's greater care for her children due to more free time.…”
Section: Discussionsupporting
confidence: 74%
“…A study from Egypt reported that children from low-income families were 38% more likely to be injured compared to middle-or high-income households [48]. This problem with the increased risk of injuries in families with lower incomes was also indicated in Iran [9]. Similar results were given in Germany by Foetinger et al [49].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Many factors, such as children’s characteristics, 4 inadequate parental supervision, 5 unsafe home environment 6 and lack of protective appliances, 7 contribute to the occurrence of home injuries in children. Home environment factors are significantly associated with occurrence of unintentional injuries in children, 8–10 and creating a safe home environment can reduce unintentional injuries among children. Young children’s bodies and awareness are not yet mature, and this is especially true for infants and toddlers; however, parents, as primary guardians, can effectively prevent the occurrence of injuries in children.…”
mentioning
confidence: 99%